Critical Issues in Higher Education - Kompf, Michael; Denicolo, Pamela M.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
The ideas and papers in this volume primarily showcase the work of a group of new scholars who will lead the next generation of educational practise and inquiry. While the topics explored are critical issues, the ways in which these new scholars have chosen to address them illustrates the diversity of voice, venue and value that has led them to present their work. Education and what it means has entered a new era in which the primary focus on education for the sake of education is strained. An educational free-for-all, in the sense of a no-holds-barred fight, seems in place as competition for market share, effective branding exercises and movement towards a client-based delivery of educational services (on demand as demanded) has been fuelled and compounded by litigation, accreditation, transfer credits and matters of patents, copyrights, ownership and monopoly. The link between education and financial well-being has been co-opted as the key to personal success. Unfortunately, the degree pursuit, often called the (3z(Bpaper chase(3y (Bhas become competitive for learners seeking scholarships, awards and entry into graduate school. This transition indicates movement from becoming well educated to employability potential paralleling much institutional retooling and sustenance of enhanced reputation and fiscal viability.s
Keywords: Education; Education; Education (general).